Electronic personal assessment questionnaire for vascular conditions (ePAQ-VAS): development and validity. Issue 8 (6th April 2020) - Aber, A; Phillips, P; Hughes, J; Keetharuth, A D; Rooney, G; Radley, S; Walters, S; Nawaz, S; Jones, G; Michaels, J
Abstract: Background: This paper describes the development and validation of an electronic personal assessment questionnaire for vascular conditions (ePAQ-VAS) that captures the symptomatology, quality of life and clinically relevant data of patients presenting to vascular services. Methods: A two-stage survey was conducted in patients attending a tertiary vascular department. Patients completed the ePAQ-VAS remotely online, or on site using an electronic tablet. In the first stage of the survey, the responses were used to perform confirmatory factor analysis to assess the construct validity and remove redundant items. The internal reliability of disease-specific scales was investigated. In the second stage of the survey, the acceptability, known-group validity, test–retest reliability, and responsiveness of ePAQ-VAS was assessed. Results: In total, 721 patients completed ePAQ-VAS. Their mean(s.d.) age was 63·5(15·7) years and 468 (64·9 per cent) were men. Some 553 patients (76·7 per cent) completed the questionnaire in clinic and the remainder completed the questionnaire online. The results of the confirmatory factor analysis confirmed the conceptual model for ePAQ-VAS structure and eliminated six items. Internal reliability was acceptable for all the scales (Cronbach's α greater than 0·7). The test–retest reliability measured by the intraclass correlation coefficient ranged from 0·65 to 0·99. The results showed that the instrument was responsive over time with the standardized response mean ranging from 0·69 to 1·60. Conclusion: ePAQ-VAS is a holistic data-collection process that is relevant to vascular service users and has potential to contribute to patient-focused care and the collection of aggregate data for service evaluation. A demonstration version of the final version of ePAQ can be viewed at http://demo-questionnaire.epaq.co.uk/home/project?id=VASC_1.7&page=1 . Graphical Abstract: This paper describes the development and validation of an electronic personal assessment questionnaire for vascular conditions (ePAQ-VAS) that captures symptomatology, quality-of-life and clinically relevant data of patients presenting to vascular services. Ready for use